A Critical Review of Algerian Universities in the Time Higher Education Ranking - Ouchen, Rima; Benbouza, Saddik; Benziane, Iman (The journal of contemporary issues in business and government, 2023)
This study examines Algerian universities’ current standing in international university rankings, with a particular focus on the Times Higher Education Rankings. The evaluation of the Top 10 universities in Algeria based on sub-indicators revealed that Algerian universities’ performance has not yet reached the standards observed in universities in the region and industrialized nations. Despite the state’s significant financial and human resources allocated to the higher education industry, as well as efforts made at all levels, the majority of universities included in the ranking were classified as 1501+ from 2018 to 2024. This study investigates the primary challenges faced by Algerian universities, the reasons for their failure to realize their full potential, and the necessary changes required to improve their standing in international ranking systems. Several significant findings have emerged from the investigation: Algerian universities have made significant advances in recent years in terms of teaching quality and scientific research; however, they continue to lag behind prominent colleges in other global regions. Algerian universities with superior academic performance are located in prominent urban areas; however, they must improve their global competitiveness by improving and developing research productivity, industrial income, and international perspective. The Algerian government should prioritize supporting universities that have achieved significant results in the sub-indicators, as these universities have the potential to contribute to improving Algeria’s overall higher education quality.